REVIEW: A real inspiration for the next generation of NZ journalists - Louise Matthews (Asia Pacific Network, 2017)
A Moral Truth: 150 years of Investigative Journalism in New Zealand, edited by James Hollings. Auckland: Massey University Press. 2017. 448 pages. ISBN: 978-0-9941-4158-3